Important elements for a framework in designing a mobile learning for English language listening and speaking skills - Subramaniam, Tamil Selvan; Md.Yunus, Melor; Mohd Ayub, Ahmad Fauzi; Rosli, Mohd.Shafie; Maaruf, Siti Zuraida; Nawi, Aliff; Palpanadan, Sarala @ Thulasi (Advance Scientific Research, 2020)
Based on a literature search, there are a number of mobile learning frameworks mentioned in a previous study that less emphasis on the major element required for English language (listening and speaking skills) specifically for level 2 students. Therefore, this paper aimed to identify the elements that fulfill their needs to be integrated in the mobile learning framework for listening and speaking skills specifically for level 2 students. This study was used quantitative research method through survey using questionnaires as the instrument to get the data and information for answering the research questions. A sample of 30 English expert teachers in the Batu Pahat district was selected based on purposive sampling method to complete the questionnaire survey given. A questionnaire that consists of four constructs was developed and the administered to obtain information. Data was collected and analyzed descriptively using SPSS (Statistical Package for The Social Sciences).. Besides, the validity was made to ensure the questionnaire can be used. Content validity, face validity and construct validity were used in this study to make sure the instrument's validity. Moreover, the pilot study was carried out to obtain the reliability of the questionnaire. Based on the analysis that has been made, Alpha Cronbach value was 0.87 categorized as a high level. Findings showed that there was an audio, graphics and text elements must be integrated into the mobile learning framework and audio elements help in listening skills while text elements help English speaking skills as well as other elements such as learning anywhere and anytime, easy to use, navigation, other resources for related information are provided, directory and help button. The findings of this study can be used by mobile learning designers as a guide in preparing for learning material and the main contribution of this study is an important element for a framework in designing a mobile learning for english language listening and speaking skills.